Infective Endocarditis by Pseudomonas Species Following Percutaneous Transluminal Mitral Commissurotomy - Rahman, MT; Mannan, MA; Ullah, M; Rahman, Z; Khair, A; Hossain, A; Sayami, LA; Ahmed, MU; Roy, SS; Masud, AA; et al. (Cardiovascular Journal, 2010)
Infective mitral valve endocarditis developed in a 35-year-old male patient after a percutaneous transvenous mitral commissurotomy (PTMC). The echocardiogram demonstrated vegetation in the anterior leaflet of the mitral valve and blood culture showed growth of Pseudomonas species which was sensitive to Ceftazidime, Ciprofloxacin, Cotrimoxazole and Imipenem and resistant to Amikacin, Ceftriaxone, Gentamycin and Nitilmycin. The patient underwent treatment with intravenous ceftazidime and ciprofloxacin for six weeks and patient improved significantly and got cure of the disease. Infective mitral valve endocarditis should be recognized as a potentially lethal complication after PTMC. The important measures to prevent bacteremia during PTMC and the appropriate role of antibiotics and operation are discussed. Keywords: PTMC; Infective endocarditis. DOI: 10.3329/cardio.v2i2.6649 Cardiovasc. j. 2010; 2(2) : 252-255